Effect of impregnation solutions on the synthesis of Ni-Cu/Al2O3 catalyst to obtain carbon nanofibers - Almiron, J (2018)
The present work reports on the influence of nickel molar loading and impregnation solutions, nitrate salts and copper and nickel ammonium complexes, on the synthesis of Ni-Cu catalyst supported on alumina for obtaining carbon nanofibers by catalytic chemical vapor deposition of methane. These catalysts were characterized by N2 adsorption-desorption, x-ray Diffraction, Thermo-Gravimetric Analysis and Scanning Electron Microscopy for the carbon nanostructures analysis.